Manual Compression Variations (Fingers vs. Fingers Assisted by Fist) and Hematoma Incidence Following Cerebral Angiography - Fritz Sumantri Usman; Andrianor Rahman; Alfi Rizky Medikanto; Engki Irawan; Agus Budi Bowo Leksono; Merlin Prisilia Kastilong; Leny Kurnia (Neurointervention Working Group of Indonesian Neurological Association, 2026)
Highlight: The FAbf technique reduced the incidence of puncture-site hematoma FAbF is an independent protective factor against hematoma ABSTRACT Introduction: Complications at the femoral access site remain a significant clinical challenge following cerebral angiography. The most common complication is an access-site hematoma resulting from inadequate hemostasis after sheath removal. Evaluating different manual compression techniques is essential to optimize bleeding control and improve patient safety. Objective: This study compared the effectiveness of standard finger compression (FC) versus the fingers-assisted-by-fist (FAbF) technique on post-procedural hematoma incidence. Method: In this single-center randomized controlled trial, 150 adult patients at PELNI Hospital, Jakarta, were allocated into two equal groups: FC (control, n=75) or FAbF (intervention, n=75). Hematoma occurrence was evaluated after sheath removal. Data were analyzed using Chi-square/Fisher’s exact tests and multivariate binary logistic regression. Result: Puncture-site hematomas occurred in 17 cases overall, with a significantly higher incidence in the FC group than the FAbF group (13 vs. 4 patients; p = 0.02; OR = 3.72; 95% CI: 1.15–12.01). Bivariate analysis also showed an association between pre-procedural antiplatelet therapy and an increased risk of hematoma (p = 0.043). Multivariate logistic regression confirmed that the compression technique was the sole independent predictor of hematoma formation; patients undergoing conventional FC were significantly more likely to develop a hematoma than those receiving FAbF (p = 0.014; aOR = 4.62; 95% CI: 1.36–15.75). Conclusion: The FAbF technique is significantly more effective than the conventional FC technique at reducing hematoma incidence following cerebral angiography with femoral access.